Association of Red Blood Cell Distribution Width With Carotid–Femoral Pulse Wave Velocity in a Southern Chinese Population - Xing Yu; Yali Huang; Yunyun Su; Liangdi Xie (The Journal of Clinical Hypertension)
ABSTRACT Red blood cell distribution width (RDW) has recently been recognized as a novel biomarker associated with various cardiovascular conditions. This study aims to investigate the relationship between RDW and carotid–femoral pulse wave velocity (cfPWV) in a southern Chinese population. A total of 4916 patients were initially enrolled from the First Affiliated Hospital of Fujian Medical University between January 2016 and December 2022. Based on the criteria of inclusion and exclusion, 2830 patients were included in this study. Body weight, height, and blood pressure were measured, and clinical biochemical tests were recorded. cfPWV was assessed using a non‐invasive automatic device. Spearman's correlation analysis, generalized linear regression analysis, multivariable logistic regression, and stratified analysis were conducted to assess the correlation between RDW and cfPWV. Participants were stratified into four subgroups based on RDW quartiles: Q1 (RDW ≤ 12.80%), Q2 (12.80% < RDW ≤ 13.40%), Q3 (13.40% < RDW ≤ 14.10%), and Q4 (RDW > 14.10%). A significant increase in age, systolic blood pressure, cfPWV, and HbA1c levels was observed with higher RDW quartiles. Both Spearman's correlation analysis and generalized linear regression analysis revealed a significant association between RDW and cfPWV. Specifically, compared to the lowest quartile, the risk of cfPWV≥10 m/s increased by 56% in the highest quartile (odds ratio = 1.564, p < 0.001). This correlation persisted particularly among the elderly, hypertensive patients who were not taking medication, and those who were taking medication but had poor control. The plasma RDW level was significantly associated with cfPWV in a southern Chinese population, particularly among older adults and individuals with hypertension, suggesting RDW as a potential marker for arterial stiffness.